Practicing the Dimensions of Social Responsibility and its Impact on the Performance of Petrochemical Companies - Durah, Omar Mohammed; Al Tijani, Mohammed Othman Al Rashid; Yafei, Salem Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
The concept of corporate social responsibility (CSR) has gained a significant interest in Sultanate of Oman in recent years. Thus, the current paper reviewed the importance of social responsibility and its role in enhancing companies performance of the petrochemical industries in the Sultanate of Oman. Two of the largest companies in this sector was selected (i.e. Omani India Fertilizer Company and Oman Gas Company). The comprehensive survey method was used where the questionnaires was distributed to all employees of the two companies. (147) of (200) questionnaires were retrieved. A descriptive and analytical approach was adopted in this study, and the data were analyzed using multiple regression analysis to test hypotheses. The results of this study indicated that the practices of social responsibility dimensions were at a high level. The economic dimension was found the highest, followed by the moral dimension, then legal dimension, then human dimension. The results indicated that the performance of companies was slightly more than average.The results also showed a significant and positive effect of only one dimension of social responsibility, namely, the human dimension on the performance, while showed no significant effect for other dimensions of social responsibility (i.e. economic, legal, and ethical dimensions).
Keywords: Social Responsibility; Economic Dimension; Legal Dimension; Ethical Dimension; Human Dimension; Performance; Petrochemical Companies; Sultanate of Oman